Cryptococcus neoformans strains isolated from church towers in Rio de Janeiro City, RJ, Brazil Cryptococcus neoformans em torres de igrejas da cidade do Rio de Janeiro, RJ, Brasil - Francisco de Assis Baroni; Claudete Rodrigues Paula; Ériques Gonçalves da Silva; Flávio Cesar Viani; Irma N.G. Rivera; Maria Tereza Barreto de Oliveira; Walderez Gambale (Revista do Instituto de Medicina Tropical de São Paulo, 2006)
Cryptococcosis has been a significant cause of morbidity and mortality in patients with Aids. Many reservoirs of the agent Cryptococcus neoformans have been reported, but the ecology of this yeast must be elucidated in order to establish surveillance programs and to prevent infections. The objective of this study was to evaluate the presence of C. neoformans in Rio de Janeiro City, RJ, Brazil. Ten churches were selected for sampling and detection of the yeast collecting pigeon dropping, air samples from church towers and neighboring areas during one year. The data demonstrated that C. neoformans has been present in every church selected and was present in 37.8% of 219 pigeon dropping samples. As well as, the yeast was isolated from soil, insects, eggs, pigeon nests and feathers. Fifteen air samples (4.9%) were positive. The growth on C.G.B. medium showed that all strains belonged to C. neoformans var. neoformans, with 98.8% of the strains belonging to serotype A. Cryptococcus neoformans é um fungo que ocasiona micose de alta morbidade e mortalidade, especialmente em pacientes com Aids. Muitos reservatórios de C. neoformans têm sido relatados, mas a ecologia desta levedura deve ser ainda elucidada para se estabelecer programas de vigilância e prevenção desta infecção. O objetivo deste estudo foi o de avaliar a presença de C. neoformans no Rio de Janeiro, RJ, Brasil. Dez igrejas foram selecionadas para este estudo, coletando-se fezes de pombo, amostras de ar, das torres das igrejas e de áreas vizinhas, durante um ano. Os resultados revelaram que C. neoformans estava presente em todas as igrejas e em 37,8% das 219 amostras das excretas das aves. Ao mesmo tempo, o fungo foi isolado do solo, insetos, ovos e ninhos de pombos. Quinze (4,9%) do total das amostras de ar foram positivas. O crescimento no meio de CGB revelou que todas as amostras pertenciam a C. neoformans var. neoformans, e 98,8% destas amostras pertenciam ao sorotipo A.